2015
DOI: 10.1089/cyber.2015.0197
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Sexual Content on Mass Media and Social Media: A Longitudinal Study

Abstract: The goal of study was to investigate whether exposure to sexual reality television content and Internet pornography is related to sexual self-presentation on social media. Based on a twowave panel survey among 1,765 adolescents aged 13-17, we found that watching sexual reality television content stimulated adolescents to produce and distribute sexual images of themselves on social media. In turn, sexual self-presentation on social media led adolescents to watch sexual reality television content more frequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 49 publications
(57 reference statements)
6
20
0
Order By: Relevance
“…This finding is a significant contribution to the objectification theory research literature: though research has shown that young women primed with selfobjectification are more likely to behave in object-like ways in the presence of others (e.g., Saguy et al, 2010), scant research has considered how young women with high levels of trait self-objectification present themselves visually to others. This finding is also consistent with existing research that has similarly linked factors associated with self-objectification (i.e., engagement with sexually objectifying media and endorsement of gender stereotypes) with sexually objectified self-presentations (van Oosten et al, 2017;Vandenbosch et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is a significant contribution to the objectification theory research literature: though research has shown that young women primed with selfobjectification are more likely to behave in object-like ways in the presence of others (e.g., Saguy et al, 2010), scant research has considered how young women with high levels of trait self-objectification present themselves visually to others. This finding is also consistent with existing research that has similarly linked factors associated with self-objectification (i.e., engagement with sexually objectifying media and endorsement of gender stereotypes) with sexually objectified self-presentations (van Oosten et al, 2017;Vandenbosch et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Current research has demonstrated links between an increased likelihood of engaging in sexualised self-presentations on social media and factors typically associated with self-objectification. Vandenbosch, van Oosten, and Peter (2015) found that engagement with sexually-objectifying media (e.g., sexual reality TV like MTV's Geordie Shore) predicted online sexualised self-presentation among young men and women.…”
Section: Self-objectification Self-presentations and Audience Reactmentioning
confidence: 95%
“…Despite these gender differences in the frequency of online sexy self-presentations, the prediction of such online behaviors by hypergender orientation was similar for boys and girls. This finding seems to be in line with previous research on predictors and consequence of social media use and online sexy self-presentations (e.g., de Vries et al, 2014Vries et al, , 2016van Oosten et al, 2015a;Vandenbosch et al, 2015). Thus, the more adolescents, female or male, endorse a hypergender orientation, the more likely they are to engage in sexy self-presentation or to look at others' sexy selfpresentation.…”
Section: Hypergender Orientation Predicts Sexy Self-presentation and supporting
confidence: 90%
“…At the same time, self-report measures have been successfully used in many previous studies on antecedents and consequences of adolescents' social media use (e.g., Barker, 2009;de Vries et al, 2016;Gross, 2004), including sexy self-presentation (e.g., Baumgartner et al, 2015). Moreover, the self-report measures of (exposure to) sexy self-presentations used in the present study have shown good construct validity, as they have been associated with other types of sexual media use (e.g., reality TV, Vandenbosch et al, 2015) and sexual attitudes (e.g., instrumental attitudes toward sex and notions of women as sex objects, van Oosten et al, 2015a) in previous studies using the same data-set and in a recent study using a different sample (van Oosten & Vandenbosch, 2017). Similarly, our self-report measure of hypergender orientation is based on validated self-report scales for hyperfemininity and hypermasculinity among adults (Mosher & Sirkin, 1984;Murnen & Byrne, 1991).…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 62%
See 1 more Smart Citation